Design research on applied Realistic Mathematics Education (RME) approach in teaching math for vocational college - Sri Imelda Edo; Wahyuni Fanggi Tasik (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
Several studies documented that mathematics, as it is taught in general secondary education, is far away from what is needed for most fields of vocational practice. Some studies found that workplace mathematics demands are very different from traditional mathematics taught in classrooms. Therefore, this study aims to design a learning trajectory for teaching mathematics in vocational college, oriented on the Realistic Mathematics Education (RME) approach to improve students' understanding and motivation in learning mathematics. Design research was chosen as an appropriate method to answer the research questions and achieve the research goals. Design research methods consist of three phases, namely preliminary design, experiment, and retrospective analysis. The research result shows that the learning trajectory can improve students' understanding. Students enjoy the learning process and give a very enthusiastic response.